An investigation of perceived behavioral control (PBC), and environmentally responsible behavior (ERB): a case study of occupants in a high performing building - Jebackumar, Swaetha, author; Valdes-Vasquez, Rodolfo, advisor; Nobe, Mary Ellen, committee member; Cross, Jennifer E., committee member (Colorado State University. Libraries, 2017)
Energy efficiency continues to be a challenge faced by the built environment. Research on determinants of energy efficiency identifies occupant behavior as the weakest link in attainment of energy efficiency goals set for high performance building designs. Environmentally Responsible Behavior (ERB) could be the answer to the improved daily functional energy efficiency of buildings. Previous studies suggest that if ERB and Perceived Behavioral Control (PBC) are positively correlated, indicating that the rate of ERB will be higher by building occupants in high performing buildings. This study focuses on the relation between ERB and PBC in regard to thermal conditions. The data used for this study comes from building occupants through an online survey, which includes both open-ended and close-ended questions that act as multi-item indicators to measure ERB, PBC, and building features. The lack of control experienced by the building occupants over the thermostat posed challenges to adequately studying the correlation between ERB and PBC in this case study. Analysis of the responses to the open–ended questions provides a better understanding of occupants' discomfort and their behavior intentions related to energy efficiency. The results of this study show that for high performance building to obtain the aggressive goals for energy efficiency, the building design not only needs to well-thought out and coordinated, but it must also meet building occupants' need for both comfort and productivity.